Online or offline? The impact of environmental knowledge acquisition on environmental behavior of Chinese farmers based on social capital perspective - Zhu, Jie; Zheng, Shiyong; Kaabar, Mohammed K. A.; Yue, Xiao-Guang (Frontiers in Environmental Science, 2022)
With the development of mobile internet, Chinese farmers have started to access diversified information through social media, on one hand based on breadth of information. On the other hand, as most farmers still live in rural areas, their socio-economic characteristics and lifestyles are in homogeneous acquaintance social network relationships, i.e. interpersonal interactions in offline homogeneous networks are still have the way for farmers to access homogeneous information (breadth of information depth). Based on social capital theory, social networks are structural social capital; trust and reciprocity are relational social capital. Further, this study divides structural social capital into connective social capital (social media access to information) and bonding social capital (offline interpersonal interaction access to information) based on the differences in their information sources. The empirical study finds that structural social capital has a positive impact on farmers' environmental knowledge acquisition which influences their environmental behavior. In addition, relational social capital (trust and reciprocity) plays a mediating role in the influence of structural social capital on farmers' environmental behavior.